THE EFFECT OF LEADERSHIP STYLE, INCENTIVES AND MOTIVATION ON EMPLOYEE WORK ACHIEVEMENT AT THE OFFICE OF THE CLEANLINESS ENVIRONMENTALAGENCY (BLHK) KOTA LANGSA - Likdanawati Likdanawati; Hamdiah Hamdiah; Saiful Harif (RADJA PUBLIKA, 2021)
This study aims to determine and analyze the Effect of Leadership Style, Incentives and Motivation on Employee Work Achievement at the Langsa City Office of Environmental Sanitation (BLHK). The research sample of 45 respondents Officer at the Office (BLHK). The variable used is the dependent variable is Employee Job Performance. while the independent variables are Leadership Style, Incentives and Motivation. This study uses multiple linear regression analysis tools. Hypothesis testing using the F test found that the variables of Leadership Style, Incentives and Motivation have a significant effect together on Employee Job Performance. While the t test or partially states that the variables of Leadership Style, Incentives and Motivation have a positive and significant effect on Employee Job Performance.